A cryogenic luminescent ratiometric thermometer based on a lanthanide phosphonate dimer - Ren, Min
The first example of a ratiometric Eu/Tb thermometer based on a lanthanide phosphonate is reported, which presents a temperature dependent emission under 393 nm excitation that enables its use as a molecular thermometer with a maximum relative sensitivity of 3.9% K-1 and a minimum temperature uncertainty of 0.15 K, both at 38 K. Additionally, the compound is a competitive luminescent colorimetric probe showing temperature dependent (x, y) CIE color coordinates changing from yellow, (0.48, 0.48) at 18 K, to red, (0.64, 0.37) at 300 K.